Research progress on key environmental drivers and comprehensive prevention and control strategies of gastric cancer - Zhang Mingyue; Wu Chuanqing (生物医学转化)
Gastric cancer (GC) remains a major global public health concern, with approximately 969000 new cases diagnosed worldwide in 2022, of which China accounted for 37%. Its incidence exhibits significant regional disparities and is closely linked to environmental factors. External environmental exposures, including poor dietary habits, smoking, and industrial pollution, contribute to carcinogenesis by disrupting the gastric mucosal barrier, inducing inflammation, and causing DNA damage. Internal environmental factors, such as Helicobacter pylori infection and gut microbiota dysbiosis, further exacerbate GC progression by activating oncogenic signaling pathways and reprogramming cellular metabolism. This review systematically analyzes and summarizes how these key environmental factors drive gastric carcinogenesis, providing a theoretical basis and practical direction for its prevention, early screening, and personalized treatment.